If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5w + 3(w + -5) = -13 Reorder the terms: -5w + 3(-5 + w) = -13 -5w + (-5 * 3 + w * 3) = -13 -5w + (-15 + 3w) = -13 Reorder the terms: -15 + -5w + 3w = -13 Combine like terms: -5w + 3w = -2w -15 + -2w = -13 Solving -15 + -2w = -13 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -2w = -13 + 15 Combine like terms: -15 + 15 = 0 0 + -2w = -13 + 15 -2w = -13 + 15 Combine like terms: -13 + 15 = 2 -2w = 2 Divide each side by '-2'. w = -1 Simplifying w = -1
| 3*2-y=9 | | 3*3-y=9 | | 4x=8+3x | | 2b^4+8b^3+8b^2=0 | | 5+4D=47 | | 6(6v+5)=1+6v | | 7x+6=9x+x | | 250+.10y=350 | | x^2+y^2+30x-2y+210=0 | | 8.5X=11 | | x+.10y=350 | | 600+600= | | 5(x+5)=-5(2x-3)+x | | 23+6y-15=62 | | 5y=x+19 | | 189s=99+10 | | 7x-18=9x+4 | | 5(y-2)=-5y+40 | | 10x=4y+16 | | -c^2-5c+66= | | 3u+37=-5(u+9) | | 10x+x-4x= | | 5x-3-x=14-3x+11 | | 2k+8-4k=28 | | -18x^2+6x+24=0 | | Z^6=1 | | 23+14s=65 | | 23s+14=65 | | 3y^2-2x^2+2xy-6=0 | | 14x+3x+7x= | | 3.2=1.35h | | 2(j-20)+3=10 |